Evaluasi Program Pos Gizi Melalui Pendekatan Empat Elemen Pemberdayaan Masyarakat: Evaluation of the Nutrition Heart Program Through the Four Elements of Community Empowerment Approach - Satyadewi, Rika; Kurnia, Galuh Mega; Ersanti, Arina Mufida; Prasasti, Corie Indria (Universitas Airlangga, 2024)
Background: The Nutrition Heart Program is a community empowerment initiative implemented to enhance the weight of toddlers based on local food capabilities. The 2024 evaluation results revealed that 46.85% of participants experienced fluctuating weight trends. Narayan's four elements of community empowerment (access to information, inclusion/participation, accountability, local organizational capacity) play a crucial role in future program enhancements. Objectives: To assess the Nutrition Heart Program based on the four elements of community empowerment. Methods: The research was conducted using a qualitative design and was conducted in 10 nutrition centers supported by Amerta Kasih. Data collection methods included in-depth interviews with cadre representatives, pregnant women, and field assistants at each nutrition center. Triangulation of methods was utilized to validate the validity of the results of data collection, namely by observation and document studies. Results: Access to information on the program includes the use of WhatsApp, flyers, field facilitators, and health workers. Most mothers of toddlers actively participated, although some were also mothers of toddlers who were passive due to work commitments. Cadres play an active role in program implementation, handling certain administrative reports are done by cadres as a form of accountability. There are no local organizations engaged in program implementation. Conclusions: Three of the four elements of community empowerment are evident in the nutrition heart program. Efforts should be made to establish or involve local organizations in program implementation of the program, as well as efforts to optimize the implementation of the other three empowerment elements.